Industrial and organizational psychology : linking theory with practice - Cooper, Cary L.; Locke, Edwin A. (Oxford : Blackwell Business, 2000)
Incentives. Workplace interventions to prevent stress-related illness. Advances in leadership training and development. The pursuit of organizational justice...
Keywords: Psychology; Organization; Industrial; Psychology, Industrial; Organizational behavior -- Psychological aspects